Deleuze and Guattari and fascism - Dolphijn, Rick; Braidotti, Rosi (Deleuze connections., 2022)
"A range of international contributors uncover and reflect upon the anti- and non-fascist ethics situated in Deleuze and Guattari's philosophical framework and that of the scholarship that followed after. The 'new philosophy' that Deleuze and Guattari propose to us is engaged and situated and it asks us to map urgent issues, not by opposing ourselves to it, but by mapping how it is part of the everyday, and of ourselves. The global rise of fascism today demands a rigid and careful analysis. The concepts and themes that Deleuze (and Guattari) handed to us in their extensive oeuvre can be of immense help in capturing its micropolitics and macropolitics."--